Ce-based organic framework enhanced the hydrogen evolution ability of ZnCdS photocatalyst. (5th January 2022) - Wang, Youzhi; Jin, Hongguang; Li, Yaopeng; Fang, Jing; Chen, Chuansheng
Abstract: Ce-based organic framework materials [UIO-66(Ce)] were prepared, and the UIO-66(Ce)/ZnCdS composite was attained by microwave irradiation. Moreover, the photocatalytic hydrogen production activity was evaluated. The experimental results revealed that the ZnCdS nanoparticle was decorated on the surface of UIO-66(Ce), and the hydrogen production ability of ZnCdS nanoparticle was improved by UIO-66(Ce) significantly. The hydrogen production yield of UIO-66(Ce)/ZnCdS reaches 3.958 mmol/g·h, in which is as about 1.95 times as that of ZnCdS (2.031 mmol/g·h). The improvement for photocatalytic hydrogen production yield is because UIO-66(Ce) can facilitate the photoinduced carriers to separating. Highlights: UIO-66(Ce) was used to improve the photocatalytic H2 production of ZnCdS nanoparticle. UiO-66(Ce)/ZnCdS composites were synthesized by a simple microwave irradiation method. The H2 production rate of the UiO-66(Ce)/ZnCdS reached 3958.8 μmol g −1  h −1 .